Equations and inequalities for secondary school students - Grebeničenkaitė, Petrė-Valda (Lietuvos matematikos rinkinys, 2001)
In this article different solution methods of equations and inequalities are reviewed. It’s necessary and useful for advanced level students preparing for the final examinations and various Olympiads and tournaments.